Development of Behavioral Counseling guidelines with Self Management Techniques to Increase Hard Work - Salawane, Hivanly; Dantes, Nyoman; Gading, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This study aims to determine the acceptance (acceptedbillity) of behavioral counseling guidelines with self-management techniques to improve students' hard work. this guide is an instrument for counselors in providing counseling guidance services in schools. The development procedure in this study follows the 4D development model which is limited to content validation testing. There are five guidance and counseling experts and practitioners who have tested the feasibility of this guide. The instrument used for the assessment consisted of 22 items that referred to the acceptance of the handbook. Analysis of the results of the assessment uses the formulation of the content validity ratio calculation from Lawshe. The results of the analysis show that the validation of the cognitive behavior counseling manual model has a content validity index (CVI) of 0.94, which means very good or special. has met the eligibility criteria to be used as an instrument in carrying out counseling guidance services.